Landasan Mutu Pendidikan Islam: Ihsan, Itqan, Amanah, dan Integritas - KELANA, SAPUTRI; SESMIARNI , ZULFANI (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2026)
Abstract: Islamic education is not solely oriented toward academic achievement but also toward the formation of students' character and spirituality. This study aims to analyze the foundations of Islamic educational quality based on the values of ihsan, itqan, amanah, and integrity, and their implementation at SLB YP Peduli Anak Nagari Akabiluru. A descriptive qualitative approach with a case study design was employed. Data were collected through semi-structured interviews with the school principal and six permanent teachers, institutional document observation, and review of the Qur'an, hadith, and indexed scientific literature. The research was conducted from January to March 2026. Analysis was carried out through data reduction, data presentation, SWOT analysis, and quality gap identification, with data validity maintained through source and technique triangulation. The findings reveal that ihsan and amanah values have been strongly internalized among teachers who continue to carry out their duties with high dedication despite limited facilities and welfare. Quality gap analysis identifies the main weaknesses in infrastructure and teacher competence, while Islamic values-based quality culture stands as the institution's primary strength. This study offers a holistic, adaptive, Qur'anic values-based Islamic educational quality model applicable to diverse Islamic educational institutions.